Association between CRP levels in systemic circulation and peri-implant bone loss - Casir, Metin; Altindal, Dicle; Cemiliraernac, Ahmet; Dundar, Serkan; Ertugrul, AbduHah Seckin (Quintessence Publishing Co Inc, 2025)
Objective: The aim of this retrospective study was to evaluate the effects of high preoperative C-reactive protein (CRP) levels on early peri-implant alveolar bone loss. Method and materials: Fifty-eight implants in 20 patients with high preoperative CRP levels and 54 implants in 20 patients with low preoperative CRP levels were evaluated. For measurement of the peri-implant alveolar bone loss, the implant platform was accepted as the reference point. On both the mesial and distal sides, the vertical distances between the reference point and the first visible bone's highest coronal level were measured. Numerical data were compared between groups using the independent sample t test or the Mann-Whitney U test. Correlations between variables were investigated with the Spearman rho test. Results: The mean CRP level of the low CRP group was 0.37 +/- 0.21 mg/L, while that of the high CRP group was 1.71 +/- 0.60 mg/L. In the high CRP group, implant failure was observed in two patients. The mesial bone loss and distal bone loss values in the group with high CRP levels were found to be significantly higher than the group with low CRP levels (P < .05). There was a significant positive correlation between the CRP levels, and distal bone loss and mesial bone loss measurements. Conclusion: The results show that high preoperative CRP levels result in an increased risk for peri-implant alveolar bone loss, and suggest that preoperative CRP levels can be important for early peri-implant alveolar bone loss.
Keywords: alveolar bone loss; C -reactive protein; dental implants; osseointegration; risk factors